Sustainability of facilities built under the Community-Led Total Sanitation (CLTS) implementation: Moving from basic to safe facilities on the sanitation ladder. - Hemez Ange Aurélien Kouassi; Harinaivo Anderson Andrianisa; Seyram Kossi Sossou; Maïmouna Bologo Traoré; Rikyelle Momo Nguematio (PLoS ONE, 2023)
In the context of monitoring progress towards SDG target 6.2, a household is counted to have access to sanitation if it uses at least basic sanitation services. Several approaches have been employed to help rural communities to climb up the sanitation ladder such as Community-led Total Sanitation (CLTS), whose primary target is to end open defecation through behavior change. CLTS does not subsidize sanitation facilities, but let households build their own facilities. The types and sustainability of facilities when construction is entrusted to households without guidelines remain understudied. The contribution of CLTS in achieving SDG6.2 also have not been studied. This paper addresses these gaps. Conducted in the province of Sissili in Burkina Faso, our study involved interviewing CLTS implementers, government officials, and community stakeholders. Coupled with household surveys, the data was analyzed using SPSS and Excel software. Findings indicate that CLTS succeeded in motivating households to build latrines hence escalating latrine coverage from 29.51% in 2016 (pre-CLTS) to 90.44% in 2020 (post-CLTS) in the province. However, 97.53% of latrines built were unimproved pit latrines with superstructures and without/with wooden or clay slabs and no roof, of which 19.76% collapsed during the rainy season. During this period, sanitation access rate rose from 11.9% to 17.00%. The study has therefore revealed that CLTS significantly elevates latrine coverage, yet it does not guarantee a proportional rise in sanitation access. This discrepancy results from the type of technologies generated by CLTS, which are not considered in calculating the sanitation access rate due to their unimproved nature. Consequently, further exploration of social approaches is essential, amalgamating technical and engineering aspects. Beyond socio-economic considerations, the sustainability of CLTS and the achievement of access to adequate and safe sanitation also rely on the robustness and resilience of the implemented facilities.